Problematic encounters between Chinese nationals and Black South Africans in the building industry in Johannesburg South Africa : an intercultural communication analysis - Ohlhoff, Heinrich (Carl Heinrich Friedrich) (University of Pretoria, 2018)
Thesis (PhD)--University of Pretoria, 2017.